Circular RNAs and immunotherapy in retinoblastoma: emerging biomarkers and precision therapeutic strategies - Wang, Xueting; Ma, Jiakang; Dang, Yalong; Lei, Fang (Frontiers in Immunology, 2025)
Retinoblastoma (RB) immunotherapy represents a paradigm shift in managing this aggressive pediatric eye cancer, overcoming limitations of conventional therapies. Recent breakthroughs reveal how circular RNAs (circRNAs) critically modulate the tumor-immune microenvironment: oncogenic circRNAs promote immune evasion by upregulating PD-L1 and suppressing T cell activity, while tumor-suppressive circRNAs such as circMKLN1 enhance antigen presentation and cytotoxic responses. The convergence of circRNA biology with immunotherapy has yielded innovative strategies, including circRNA-targeted immune checkpoint blockade to reverse T cell exhaustion, circRNA-engineered CAR-T cells with improved tumor homing and persistence, and circRNA-based oncolytic viruses that stimulate immunogenic cell death. Notably, exosomal circRNAs serve dual roles as both immune modulators and minimally invasive biomarkers for predicting immunotherapy response. While preclinical studies demonstrate remarkable synergy between circRNA inhibition and PD-1/CTLA-4 blockade in RB models, clinical translation requires optimization of delivery systems and combinatorial regimens. This review summarizes the latest evidence positioning circRNAs as central regulators of anti-tumor immunity and provides a strategic roadmap for the integration of circRNA-based approaches in precision immunotherapy for RB.